Formaldehyde content and quality characteristics of selected fish and seafood from wet markets - Nordin, Noordiana; Abu Bakar, Fatimah; Che Baharom, Farhana Yasmeen (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
Formaldehyde was used by fishermen and fish vendors to preserve the freshness and quality of fish and seafood. The study was undertaken to determine the formaldehyde content and quality characteristics of fish and seafood from wet markets. Formaldehyde content was in the range of 0.38 to 15.75 μg g-1. Three types of biogenic amines (histamine, putrescine and cadaverine) were detected from all samples in which histamine content ranged from 0.25 to 1.97 μg g-1, putrescine from 0.33 to 9.09 μg g-1 and cadaverine from 0.34 to 5.81 μg g-1. Amino acids as biogenic amines precursor were also determined with lysine ranged from 12.75 to 28.80mg g-1, arginine from 8.17 to 27.83 mg g-1 and histidine from 1.93 to 10.14 mg g-1. As for the microbiological analyses, total plate counts for all fish types ranged from 5.68 to 7.13 log cfu g-1 and the proteolytic counts from 5.12 to 6.91 log cfu g-1. Samples were also analyzed for the presence of putrescine/ cadavarine/ histamine producing bacteria where the counts ranged from 3.50 to 6.52 log cfu g-1. The pH of all selected fish ranged from 6.25 to 7.28. There was no significant difference (p>0.05) among fish purchased from different wet markets. Hence this study suggested that fish and seafood from wet markets can be considered in good quality since the formaldehyde content and microbiological counts were still below the permissible limits.